Diversifikasi Menu Makanan Menggunakan Sumber Pangan Lokal:Undur-Undur Laut - Hidayat, Muhammad Syamsu; Suwandojo, Dodik Prakoso Eko Hery (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
Mole crabs are abundant marine resources found along the southern coast of Java Island. However, their economic value remains relatively low. Local residents are still limited to selling mole crabs in simple forms such as deep-fried batter or traditional peanut crackers (peyek). In order to increase their market value, product diversification is necessary. In this community service activity, we provided training on processing mole crabs into Padang sauce, butter sauce, and salted egg sauce dishes. Participants showed strong enthusiasm during the training. They gained new knowledge and plan to offer these processed products in their restaurants. However, to create demand for processed mole crab products, intensive promotional support is required, as mole crabs are not a commonly consumed food source among tourists. The involvement of local government and business actors is crucial in stimulating tourist demand